Coupled Strengthening Effects by Lattice Distortion, Local Chemical Ordering, and Nanoprecipitates in Medium-Entropy Alloys - Cheng, Wenqiang; Yuan, Fuping; Wu, Xiaolei (Frontiers in Materials, 2021)
Extraordinary mechanical properties can be achieved in high entropy alloys (HEAs) or medium entropy alloys (MEAs) with nanoprecipitates. In the present study, the extra coupled strengthening effects by lattice distortion, local chemical ordering and nanoprecipitates in the HEAs and MEAs with nanoprecipitates have been systematically investigated by large-scale molecular dynamics simulations. The moving of the dislocation can be slowed down and the dislocation line shows wavy configuration due to lattice distortion and local chemical ordering, resulting in strengthening. The degree of the wavy configuration increases and the sliding velocity of the dislocation decreases with increasing degree of local chemical ordering. It is clearly indicated that the dislocation moves via nanoscale segment detrapping mechanism due to the effects of lattice distortion and local chemical ordering, resulting in roughened dislocation pathways for strengthening. The activated nanoscale segments are observed to be more easily to detrap from the regions with stronger Co-Cr local chemical ordering and then propagate into the regions without such chemical ordering. This moving characteristics of the dislocation can delay the unpinning process from nanoprecipitates, thus extra coupled strengthening effect has been revealed in the HEAs and MEAs with nanoprecipitates compared to the pure Orowan’s strengthening.